Application of multiphase reaction engineering and process intensification to the challenges of sustainable future energy and chemicals. (10th January 2017) - Powell, Joseph B.
Abstract: Multiphase reaction engineering and process intensification can play a critical role in developing technologies to unlock the value and opportunities of shale gas, and to mitigate carbon footprints in providing sustainable options for future energy and chemicals. New and intensified reactor designs and separation systems will be essential for efficient methane conversion, biomass upgrading to fuels and chemicals, as well as for affordable carbon capture. The following review summarizes future energy challenges, and assesses the state of the art of chemical engineering science in providing the necessary tools for more rapid, efficient, and reliable technology development and scale up. Highlights: Multiphase reaction engineering and process intensification are key tools for addressing future energy challenges. A priori prediction of reactor, catalyst, and separations-system performance can speed process development and deployment. Improved tools are needed for prediction of complex, multiphase and multicomponent systems, including trace chemistry. Laboratory reactor and pilot plant expertise remains an important skill for industry.